German Law Reform Does Not Reduce the Prevalence of Coercive Measures in Residential Institutions for Children, Adolescents, and Young Adults With Intellectual and Developmental Disabilities - Geissler, Julia M.; Werner, Elisabeth; Dworschak, Wolfgang; Romanos, Marcel; Ratz, Christoph (Frontiers in Psychiatry, 2021)
Background: Approximately 10% of children, adolescents and young adults with an intellectual and developmental disabilitiy (IDD) in Bavaria live in residential institutions. 2015 saw media reports raising suspicions about excessive use of coercive measures (cM) in those institutions. Until a law reform at the end of 2017 made permission from family courts mandatory for cM, their use was governed by parental consent. The REDUGIA project conducted a representative survey comparing cM and their relation to challenging behavior (cB) and employee stress pre and post reform. Methods: We sent questionnaires to 65 residential institutions for children, adolescents and young adults with IDD in 2017 (pre reform, T1) and 2019 (post reform, T2). To assess changes, we analyzed data from all available questionnaire pairs (T1 and T2, N=43). We calculated paired t-test and correlative analyses concerning the relationship between cB, cM, and employee stress. Results: The number of residents overall (T1: N=1661; T2: N=1673) and per institution (T1: m=38.6±32.0; T2: m=38.9±34.5, p=0.920) remained stable. We did not see any changes in the Index cB (p=0.508) or the proportion of residents per institution displaying various types of challenging behaviours (all ps>0.220). There was no change in the Index cM (p=0.089) or any indicator of employee stress, all ps>0.323. At follow-up, the Index cB correlated positively with the Index cM (r=0.519 p<0.001). Regarding employee stress, the Index cB correlated positively with the frequency of sick leave (r=0.322, p=0.037) and physical attacks on employees (r=0.552, p<0.001). The Index cM also correlated positively with the frequency of sick leave (r=0.340, p=0.028) and physical attacks on employees (r=0.492, p=0.001). Discussion: Coercive measures are not a general phenomenon, but are focused on specialized institutions. The law reform did not lead to changes in the number of children, adolescents and young adults with IDD affected by coercive measures in residential institutions in Bavaria. There were still large discrepancies between institutions in the prevalence of challenging behavior and coercive measures. Coercive measures were associated with challenging behavior and employee stress. Taken together, findings from REDUGIA emphasize the need to prevent challenging behavior and thus coercive measures.